2016
DOI: 10.1051/0004-6361/201527056
|View full text |Cite
|
Sign up to set email alerts
|

[O III] line properties in two samples of radio-emitting narrow-line Seyfert 1 galaxies

Abstract: The [O III] λλ 4959, 5007 lines are a useful proxy to test the kinematic of the narrow-line region (NLR) in active galactic nuclei (AGN). In AGN, and particularly in narrow-line Seyfert 1 galaxies (NLS1s) these lines often show few peculiar features, such as blue wings, often interpreted as outflowing component, and a shift − typically toward lower wavelengths − of the whole spectroscopic feature in some exceptional sources, the so-called blue outliers, which are often associated to strong winds. We investigat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
49
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 67 publications
7
49
0
Order By: Relevance
“…In fact, since CSS/HERGs display lobes that are already developed (Orienti 2016), this means that the extended radio emission form even in very young ages, which in turn implies the rejection of the radio-quiet hypothesis. This conclusion is in agreement with the results of Berton et al (2016b), where the observed differences in narrow-line region properties points in the same direction.…”
Section: Evolutionary Picturesupporting
confidence: 93%
“…In fact, since CSS/HERGs display lobes that are already developed (Orienti 2016), this means that the extended radio emission form even in very young ages, which in turn implies the rejection of the radio-quiet hypothesis. This conclusion is in agreement with the results of Berton et al (2016b), where the observed differences in narrow-line region properties points in the same direction.…”
Section: Evolutionary Picturesupporting
confidence: 93%
“…By combining these optical data with archival radio, infrared (WISE), γ-ray (Fermi) data and X-ray data taken via a ToO observation with X-ray Telescope (XRT) on board the Swift satellite, Tanaka et al (2014) revealed the similarity of this object's SED to those of the radio/γ-ray-loud NLS1s, although the large [O III]/Hβ flux ratio does not satisfy the general criteria for NLS1s. Flux ratio between the [O III] emission lines and radio emission is also consistent with those of radio-loud NLS1s (Berton et al 2016).…”
Section: Introductionsupporting
confidence: 79%
“…This might indicate that more sources of this kind could be found among RQ objects. Very few RQNLS1s show detectable jets or diffuse radio emission (Berton et al 2016b). This is partly because they are by definition faint in the radio regime, but some objects that fit the RQ definition show nonthermal core emission when observed with high sensitivity (Giroletti & Panessa 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This broad component is clearly visible in all the permitted lines of the optical spectrum. Conversely, narrow lines, and particularly [O III]λ5007, do not show any outflowing component and are well reproduced by a single Gaussian profile (Berton et al 2016b).…”
Section: Mrk 783mentioning
confidence: 96%